On (M,P)-functions with some features and new inequalities - Erhan Set; Ali Karaoğlan; İmdat İşcan; Neslihan Kılıç (Miskolc Mathematical Notes)
In this study, we introduce a generalization of P(M,P)(M,P)(M,P)M